Identification of ganglioside GM2 activator playing a role in cancer cell migration through proteomic analysis of breast cancer secretomes. Issue 6 (27th April 2016) - Shin, Jihye; Kim, Gamin; Lee, Jong Won; Lee, Ji Eun; Kim, Yoo Seok; Yu, Jong‐Han; Lee, Seung‐Taek; Ahn, Sei Hyun; Kim, Hoguen; Lee, Cheolju
Abstract : Cancer cell secretomes are considered a potential source for the discovery of cancer markers. In this study, the secretomes of four breast cancer (BC) cell lines (Hs578T, MCF‐7, MDA‐MB‐231, and SK‐BR‐3) were profiled with liquid chromatography–tandem mass spectrometry analysis. A total of 1410 proteins were identified with less than 1% false discovery rate, of which approximately 55% (796 proteins) were predicted to be secreted from cells. To find BC‐specific proteins among the secreted proteins, data of immunohistochemical staining compiled in the Human Protein Atlas were investigated by comparing the data of BC tissues with those of normal tissues. By applying various criteria, including higher expression level in BC tissues, higher predicted potential of secretion, and sufficient number of tandem mass spectra, 12 biomarker candidate proteins including ganglioside GM2 activator (GM2A) were selected for confirmation. Western blot analysis and ELISA for plasma samples of healthy controls and BC patients revealed elevation of GM2A in BC patients, especially those who were estrogen receptor‐negative. Additionally, siRNA‐mediated knockdown of GM2A in BC cells decreased migration in vitro, whereas the overexpression of GM2A led to an increase in cell migration. Although GM2A as a diagnostic and prognostic marker in BC should be carefully verified further, this study has established the potential role of GM2A in BC progression. Abstract : Our integrated approach using the secretome analysis for BC cancer cells and publicly available datasets, allowed selection of candidate biomarkers of BC. Of the 12 candidate biomarkers of BC, we were able to show that GM2A plays a key role in migration of BC cells in the current study. Although, Western blot and ELISA data do not provide strong evidence that GM2A is useful as a screening marker for BC, we were able to find that both specificity and sensitivity of GM2A were increased for ER negative patients in comparison with ER positive patients.